2019
DOI: 10.4049/jimmunol.1800504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Subpopulations of Chicken Mononuclear Phagocytes That Express TIM4 and CSF1R

Abstract: The phosphatidylserine receptor, TIM4, encoded by TIMD4, mediates the phagocytic uptake of apoptotic cells. We applied anti-chicken TIM4 monoclonal antibodies, in combination with CSF1R reporter transgenes to dissect the function of TIM4 in the chick (Gallus gallus). During development in ovo, TIM4 was present on the large majority of macrophages but expression became more heterogeneous post-hatch. Blood monocytes expressed KUL01, class II MHC and CSF1R-mApple uniformly. Around 50% of monocytes were positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 61 publications
3
49
0
Order By: Relevance
“…Several receptors, such as T cell membrane protein 4 (TIM4) [48], receptor tyrosine kinase Mer (MerTK) [49], and mannose receptor [50], are known for their important role in the recognition and phagocytosis of apoptotic cells and pathogens in mice. Similarly, the role of TIM4 in phagocytosing apoptotic cells has been reported in chickens [18]. Therefore, the higher phagocytic activity of MRC1 hi MHCII lo cells compared to that of MRC1 lo MHCII hi cells is likely linked to the expression level of MRC1, a chicken mannose receptor [14].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several receptors, such as T cell membrane protein 4 (TIM4) [48], receptor tyrosine kinase Mer (MerTK) [49], and mannose receptor [50], are known for their important role in the recognition and phagocytosis of apoptotic cells and pathogens in mice. Similarly, the role of TIM4 in phagocytosing apoptotic cells has been reported in chickens [18]. Therefore, the higher phagocytic activity of MRC1 hi MHCII lo cells compared to that of MRC1 lo MHCII hi cells is likely linked to the expression level of MRC1, a chicken mannose receptor [14].…”
Section: Discussionmentioning
confidence: 68%
“…Chicken monocyte/macrophage lineage cells expressing MRC1 have been found to exhibit features similar to those in mammals, including morphological features [15], plasticity [16], and capability for phagocytosis [17,18]. Furthermore, they express several TLRs, and the activation of TLRs by their ligands induces bacterial lysis [19] and pro-inflammatory cytokine secretion [20], suggesting that they induce a similar response during inflammation compared to that of mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MHC-II low monocyte population is increased under inflammatory conditions induced by intraperitoneal LPS injection [ 42 ]. On the other hand, Hu and collaborators also demonstrated the monocytes heterogeneity and separated blood monocytes into two subpopulations based on the expression of TIM4 (a receptor that binds to phosphatidylserine) [ 19 ]. It would be of great interest to determine whether MHC-II downregulation occurs in both subpopulations or if it is restricted to one population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in chickens (also demonstrated in humans and mice) have shown that in response to a biological stimulus, macrophages and other cells of the immune system secrete pro- and anti-inflammatory cytokines that are released into the circulatory system to elicit a systemic immune response [ 13 16 ]. One of the target populations of these cytokines is monocytes, described as a heterogeneous population in the avian system, which have chemotactic and phagocytic activities and are capable of generating a respiratory burst [ 17 19 ]. During infectious or severe inflammatory insult in humans and mice, this population has an important role in compensatory anti-inflammatory response syndrome (CARS), a biological process that is necessary to prevent overwhelming inflammation and avoid organ failure [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, T-cell membrane protein 4 (TIM4) is a receptor expressed primarily by macrophages, binds to phosphatidylserine, and most likely participates in the recognition and clearance of apoptotic cells ( 89 ). Hu and colleagues applied anti-chicken TIM4 monoclonal antibodies in combination with colony stimulating factor 1 receptor reporter transgenes to dissect the function of TIM4 in the chick ( 90 ). They demonstrated that TIM4 was present on the large majority of macrophages during development in ovo and to be expressed also by other cells with phagocytic activity, such as dendritic cells, after hatching ( 90 ).…”
Section: The Chick Embryo Chorioallantoic Membranementioning
confidence: 99%